Pneumocystis jirovecii Can Be Productively Cultured in Differentiated CuFi-8 Airway Cells - Verena Schildgen (American Society for Microbiology, 2014)
ABSTRACT Although Pneumocystis jirovecii is a well-known and serious pathogen, all previous attempts to isolate, cultivate, and propagate this fungus have failed. This serious challenge in microbiology was addressed in the present study. We examined whether P. jirovecii could be cultured in a permanent three-dimensional air-liquid interface culture system formed by CuFi-8 cells, a differentiated pseudostratified airway epithelial cell line. Cultured pseudostratified cells were inoculated with bronchoalveolar fluid that had been confirmed to be positive for P. jirovecii using PCR. Five days later, the cells and basal medium were harvested and tested for P. jirovecii using quantitative PCR (qPCR), commercially available immunofluorescence detection assays, and Grocott staining of formalin-fixed, paraffin-embedded thin sections of infected-cell cultures. We successfully productively cultivated and propagated P. jirovecii from these P. jirovecii-positive bronchoalveolar lavage fluid (BALF) samples. Furthermore, we provide evidence that P. jirovecii induced cytopathic effects on lung epithelial cells and was even invasive in cell culture. To the best of our knowledge, the cell culture system developed herein represents the first methodology to enable molecular analyses of this pathogen’s life cycle and further in vitro studies of P. jirovecii, such as assessments of drug sensitivity and resistance as well as investigations of the pathogen’s stability against environmental factors and disinfectants. IMPORTANCE This is the first report of the successful productive cultivation and propagation of Pneumocystis jirovecii, a human-pathogenic fungus of major clinical significance. These findings are groundbreaking because they will influence the field of diagnostic microbiology, facilitate the testing of antibiotics against P. jirovecii, and enable stability studies of this pathogen when exposed to the environmental factors and chemicals that hospitals are required to use for disinfection. Because productively culturing P. jirovecii has been attempted unsuccessfully for several decades, this study represents a breakthrough in this field.